The Super Secret Octagon Valley Society - Book 1 - De la Cruz, Melissa, 1971- (Los Angeles : Disney/Hyperion, 2023)
"Eight singular middle schoolers from across America find themselves belonging in a series of escape room-type challenges. Each sixth grader assumes that winning a coveted spot to spend three days at the Octagon Valley Institute led by Willy Wonka-esque Onasander Octagon--an ethnically ambiguous multiracial tech genius--means winning a 'golden ticket to the rest of your life.' However, they soon realize that instead of an academic conference, they will each have to utilize their particular skills to find eight puzzle pieces in a high-stakes scavenger hunt"--|cProvided by publisher.
Keywords: Middle school students -- Juvenile fiction; Escape rooms -- Juvenile fiction; Secret societies -- Juvenile fiction; Friendship in adolescence -- Juvenile fiction; Treasure hunting -- Juvenile fiction; Middle school students -- Fiction; Escape rooms -- Fiction; Secret societies -- Fiction; Friendship -- Fiction; Treasure hunt (Game) -- Fiction; Junior fiction